2000
DOI: 10.1111/j.1553-2712.2000.tb01257.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Digoxin vs Calcium Alone for Severe Verapamil Toxicity

Abstract: Abstract. Calcium chloride (CaCl 2 ) is ineffective in severe calcium channel antagonist overdoses. Digoxin increases intracellular calcium by inhibiting the sodium-potassium adenosine triphosphatase enzymes. Objective: To examine the effect of calcium and digoxin on the treatment of verapamil toxicity. Methods: Sixteen dogs were instrumented to monitor hemodynamics. Verapamil toxicity (50% decrease in mean arterial pressure) was induced with verapamil (VER) at 6 mg/kg/hr and maintained for 30 minutes by titra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 10 publications
(16 reference statements)
0
13
0
Order By: Relevance
“…Digoxin, like other cardiac glycosides, inhibits the sodium-potassium ATPase pump, thereby increasing the intracellular sodium concentration (1)(2)(3)(4)(5). The increased intracellular sodium inhibits sodium-dependent calcium transport out of the cytoplasm, resulting in increased intracellular calcium, and thus increased inotropy.…”
Section: Introductionmentioning
confidence: 99%
“…Digoxin, like other cardiac glycosides, inhibits the sodium-potassium ATPase pump, thereby increasing the intracellular sodium concentration (1)(2)(3)(4)(5). The increased intracellular sodium inhibits sodium-dependent calcium transport out of the cytoplasm, resulting in increased intracellular calcium, and thus increased inotropy.…”
Section: Introductionmentioning
confidence: 99%
“…13 We previously demonstrated that a high therapeutic dose of digoxin (0.018 mg/kg, or two times the loading dose of digoxin) plus calcium (200 mg/kg) increased systolic blood pressure by 15% to 21% versus calcium alone in a model of severe verapamil toxicity (25 mg/kg over 4 hours). 3 Additionally, neither ventricular tachycardia nor ventricular fibrillation occurred in the digoxin group. A similar result was found in a model of mild-to-moderate verapamil toxicity (4 mg/kg over 30 minutes) treated with calcium (7.5 mg/kg) plus digoxin (0.009 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…5 The verapamil infusion rate and titration period previously used to achieve toxicity were used to induce verapamil toxicity. 3,5 At the end of the verapamil toxicity phase, defined as time zero, the animals received a dose of digoxin, and the verapamil infusion was changed to 4 mg/kg/ hr and continued for five hours to simulate continuous gastrointestinal absorption from a large oral ingestion. Each dog received one dose of digoxin equivalent to 1, 1.5, 2, 3, 4, 6, or 8 times the loading dose of digoxin (0.009 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations